2009
DOI: 10.1159/000162296
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Intervention for Premenstrual Syndrome: A Meta-Analysis of Randomized Controlled Trials

Abstract: Background: We conducted a systematic review and meta-analysis to determine the efficacy of psychological interventions for premenstrual syndrome. Methods: We systematically searched and selected studies that enrolled women with premenstrual syndrome in which investigators randomly assigned them to a psychological intervention or to a control intervention. Trials were included irrespective of their outcomes and, when possible, we conducted meta-analyses. Results: Nine randomized trials, of which 5 tested cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 42 publications
2
46
1
5
Order By: Relevance
“…So far, only a few studies have investigated the efficacy of CBT and the potential of iCBT for PMDD [21, 22]. Although previous results were promising, there is a lack of methodologically profound studies investigating the efficacy of a CBT for PMDD [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, only a few studies have investigated the efficacy of CBT and the potential of iCBT for PMDD [21, 22]. Although previous results were promising, there is a lack of methodologically profound studies investigating the efficacy of a CBT for PMDD [48].…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive-behavioural therapy (CBT) is the psychological approach with the best evidence of efficacy. Two previous meta-analyses have reported promising results for CBT based on 5 [21] or 6 controlled trials [22]. However, the methodological quality of these trials is rather low.…”
Section: Introductionmentioning
confidence: 99%
“…Effect size can be conservatively grouped according to Cohen [30] as small (0.2), medium (0.5) or large (0.8). For an easier interpretation, we further transformed effect sizes of the main outcomes into numbers needed to treat (NNT) according to the procedure of Busse et al [31] (based on the results of Norman et al [32]) and presented them additionally as odds ratios (OR).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown the efficacy of psychological therapies in different medical illnesses [13,14,15,16]. Some investigations have been carried out which focus on the psychological aspect of lupus, with the aim of reducing the disease’s interference in the daily life of patients [17], improving social support and patients’ levels of self-management [18,19,20] and developing coping skills in patients [21].…”
Section: Introductionmentioning
confidence: 99%